Kesulitan Siswa SMP Dalam Pemecahan Masalah Matematis - Samsul Hadi (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2020)
Problem solving is one of the competencies of students developed in the mathematics learning curriculum in dealing with every problem both in learning and in everyday life. The focus of this research is to get a picture of the difficulty of students in solving mathematical problems in one of the State Junior High Schools in East Lombok district, NTB, Indonesia. Participants in this study were 29 students of class VIII consisting of 14 male students and 15 female students in the 2017/2018 school year. The selection of participants was done by purposive sampling. The research methodology used is a qualitative approach using test instruments for problem solving skills, interviews, observations, and documentation studies. The results showed that: (1) students were not able to understand, identify, and interpret problems properly, (2) students were not able to make representations of problems into mathematical models, (3) students were not able to carry out problem solving strategies that had been made correctly, (4) students are not able to do calculations correctly and thoroughly, (5) all students are not able to make alternative strategies for solving problems, and (6) almost all students are indicated difficulties in aspects of language, a quarter of students in aspects of concepts/modeling, and almost half the students in applied aspects.